Prevalence and predictors of oral to intravenous antibiotic switch among adult emergency department patients with acute bacterial skin and skin structure infections: a pilot, prospective cohort study. Issue 8 (30th August 2020) - Quirke, Michael; Mitchell, Niamh; Varley, Jarlath; Kelly, Stephen; Boland, Fiona; Moughty, Adrian; McKeever, Joseph; Fahey, Tom; Wakai, Abel
Abstract : Objective: To determine the prevalence and predictors of oral to intravenous antibiotic switch among adult emergency department (ED) patients with acute bacterial skin and skin structure infections (ABSSSIs). Design: Multicentre, pilot cohort study. Setting: Three urban EDs in Dublin, Ireland. Participants: Consecutive ED patients aged >16 years old with ABSSSIs between March 2015 and September 2016. Intervention: Oral flucloxacillin 500 mg–1 g four times a day (alternative in penicillin allergy). Primary and secondary outcome measures: The primary outcome was to determine the prevalence and predictors of oral to intravenous antibiotic switch. Secondary outcomes were to determine the prevalence and predictors of receiving an extended course of oral antibiotic treatment and measurement of interobserver reliability for clinical predictors at enrolment. Results: Overall, 159 patients were enrolled of which eight were lost to follow-up and five were excluded. The majority of patients were male (65.1%) and <50 years of age (58.2%). Oral to intravenous antibiotic switch occurred in 13 patients (8.9%; 95% CI 4.8% to 14.7%). Increased lesion size (OR 1.74; 95% CI 1.09 to 2.79), white cell count (OR 1.32; 95% CI 1.05 to 1.67), athlete's foot (OR 8.00; 95% CI 2.31 to 27.71) and fungal nail infections (OR 7.25; 95% CI 1.99 to 26.35) were associated with oral to intravenous antibiotic switch. 24.8% (95% CI 18.1% to 33.0%) of patients received an extended course of oral antibiotic treatment. Conclusion: The prevalence of oral to intravenous antibiotic switch in this pilot study is 8.9% (95% CI 4.8% to 14.7%). We identify the predictors of oral to intravenous switch worthy of future investigation. Trial registration number: NCT02230813 .